Are you measuring the impacts and outcomes of your professional doctorate programme?. Issue 2 (4th May 2019) - McSherry, R.; Bettany-Saltikov, J.; Cummings, E.; Walker, K.; Ford, K.; Walsh, K.
ABSTRACT: The aim of the paper is to report some of the research findings from a workshop held at an International Professional Doctorate Conference. The workshop aimed to elicit the views of attendees surrounding the following questions: How do you currently measure the impact and outcome of your professional doctorate programme(s)? What tools, frameworks, benchmarks, guidelines do you know currently exist? How could we better measure the impact and outcome of the professional doctorate programme(s)? A qualitative research design was applied. Thirty self-selecting participants attended the workshop. Thematic Analysis identified 31 organisational themes and 5 global themes. These related to (1) defining and operationalising the terms impact and outcome for professional doctorate programmes (PDP); (2) Recognising and respecting the difference, diversity and variety of impact and outcome measures; (3) Designing a 360° stakeholder approach to PDP evaluation; (4) Sharing and Dissemination post-completion; (5) Recognising formal and informal external validation. The originality and significance of this research is in sequencing the impact and outcome measures of professional doctorate programmes and in identifying the approaches that could be taken to track and evaluate a programme both before, during and on completion. Furthermore, the newly devised 360° stakeholder approach to PDP evaluation is original in two ways. It incorporates the personal, organisational, professional and employer (POPE) approach and also acknowledges the importance of a comprehensive longitudinal evaluation, pre, throughout and beyond the programme.